Comparison between PEEK and Ti6Al4V concerning micro-scale abrasion wear on dental applications. (July 2016) - Sampaio, M.; Buciumeanu, M.; Henriques, B.; Silva, F.S.; Souza, J.C.M.; Gomes, J.R.
Abstract: In the oral cavity, abrasive wear is predictable at exposed tooth or restorative surfaces, during mastication and tooth brushing. Also, wear can occur at contacting surfaces between the Ti-based prosthetic structures and implants in presence of abrasive compounds from food or toothpaste. Thus, the aim of this work was to compare the abrasive wear resistance of PEEK and Ti6Al4V on three-body abrasion related to different hydrated silica content and loads. Surfaces of Ti6Al4V or PEEK cylinders (8 mm diameter and 4 mm height) were wet ground on SiC papers and then polished with 1 µm diamond paste. After that, surfaces were ultrasonically cleaned in propyl alcohol for 15 min and then in distilled water for 10 min. Micro-scale abrasion tests were performed at 60 rpm and on different normal loads (0.4, 0.8 or 1.2 N) after 600 ball revolutions using suspensions with different weight contents of hydrated silica. After abrasive tests, wear scars on flat samples were measured to quantify the wear volume and characterized by scanning electron microscope (SEM) to identify the dominant wear mechanisms. Results showed a higher volume loss rate on PEEK than that recorded on Ti6Al4V, , when subjected to three-body abrasion tests involving hydrated silica suspensions. An increase in volume loss was noted on both tested materials when the abrasive content or load was increased. PEEK was characterized by less wear resistance than that on Ti6Al4V after micro-scale abrasion wear in contact with hydrated silica particles, as commonly found in toothpastes. Graphical abstract: Highlights: PEEK samples were synthesized by hot-pressing technique. PEEK revealed lower wear rate under two-body abrasion than Ti6Al4V. The wear rate of Ti6Al4V was lower than PEEK in three-body abrasion.